2013
DOI: 10.1080/10967494.2013.849156
|View full text |Cite
|
Sign up to set email alerts
|

Vive la Différence? The Impact of Diversity on the Turnover Intention of Public Employees and Performance of Public Agencies

Abstract: This article addresses previous shortcomings in diversity management scholarship by testing an expanded diversity model borrowed from the work of Page (2007). Page's model assumes diversity can be measured as both a mean and a variance, and that it consists of cognitive, identity, and preference characteristics. We link Page's conceptualization of diversity to both individual-level outcomes and organizational performance. Results indicate cognitive, preference, and identity diversity have either no or small, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 81 publications
3
19
0
Order By: Relevance
“…This findings was consistent with the past empirical study conducted by Langbein & Stazyk, 2013;Pitts, 2006;Hammer et al, 2008, stated that the positive workplace diversity and work life balance tends to increase employee satisfaction and retention rate of an organization. The incorporation between working field and family bonding would certainly raise employee satisfaction (Nadia, Syed & Humer, 2011).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This findings was consistent with the past empirical study conducted by Langbein & Stazyk, 2013;Pitts, 2006;Hammer et al, 2008, stated that the positive workplace diversity and work life balance tends to increase employee satisfaction and retention rate of an organization. The incorporation between working field and family bonding would certainly raise employee satisfaction (Nadia, Syed & Humer, 2011).…”
Section: Resultssupporting
confidence: 82%
“…Researchers (Pitts, 2006;Kellough & Naff 2004;Naff & Kellough 2003) found that workplace diversity enhances an employee's efficiency, organizational achievement and persistent competitiveness. Hence, matching the organizational mission with workplace diversity tends to escalate employee satisfaction and retention, increases responsiveness and certainly adds value to the final consumers (Langbein & Stazyk, 2013;Pitts, 2006).…”
Section: Operationalization Of Research Variablesmentioning
confidence: 99%
“…One possible interpretation is that the diversity climate may not be sufficient for gender- and age-diverse employees to achieve their optimal identifications by balancing the need for uniqueness and the need for belongingness. Scholars have discussed a variety of other contextual factors, such as transformational leadership, management discretion, employee voice, and organizational fairness (Langbein & Stazyk, 2013; Opstrup & Villadsen, 2015; Shore et al, 2011), which may lead employees in highly gender- and age-mixed workforces to feel that their full range of social identities are accepted and appreciated. These human resource management policies and practices may warrant additional attention from researchers and practitioners seeking to create supportive diversity climates for gender- and age-diverse employees.…”
Section: Discussionmentioning
confidence: 99%
“…A recognition of the salience of this point has been embedded in representative bureaucracy scholarship, which presumes that public organizations staffed with diverse employees benefit from having a wide range of knowledge, skills, and abilities upon which to draw when making decisions about the design and implementation of public policies (Riccucci 2002;Pitts and Wise 2010;Portillo 2010;Langbein and Stazyk 2013 research assumes that minority and under-represented groups possess qualitatively different values and experiences that are often marginalized in predominantly white, male organizations. When organizations are staffed with larger proportions of diverse employees, it becomes more likely that minority and under-represented groups will influence policies in ways that reflect their own value preferences.…”
Section: Minority Status Public Values and Decision-makingmentioning
confidence: 99%
“…The extent to which organizational and individual public values systems differ probably has widespread implications for citizens and the activities of organizations. For instance, diversity management and representative bureaucracy scholarship argue that having a diverse set of values and value preferences in public organizations will improve decision‐making (Langbein and Stazyk ). Alternatively, public administration research also indicates that organizational and individual value systems must overlap for employees to remain committed to and engaged in their organizations (Kristof‐Brown ; Bright ; Steijn ; Wright and Pandey ).…”
Section: The Importance Of Values To Managementmentioning
confidence: 99%